Impact of Early Childhood Caries and Maternal Behaviors on Oral Health-Related Quality of Life of Children - Joanna Tatith Pereira; Jessica Klöckner Knorst; Patrícia Blaya Luz; Inaiá Bonfadini; Monique Scapinello; Fernando Neves Hugo; Fernando Borba de Araujo (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the impact of early childhood caries, maternal behaviors and associated factors on the oral health-related quality of life (OHRQoL) of preschool children. Material and Methods: This cross- sectional study was conducted with 163 preschool children aged 3-4 old from Porto Alegre, Southern Brazil. Mothers completed the Brazilian version of the Early Childhood Oral Health Impact Scale (ECOHIS) and answered questions about sociodemographic and maternal behaviors characteristics. The severity of dental caries was assessed by ICDAS criteria for evaluated early childhood caries (ECC). A Poisson regression model was used to investigate the association of ECC and associated factors on OHRQoL. Results: A total of 91.4% of preschooler children was ECC (ICDAS ≥ 1). Mean ECOHIS function domain and parental anxiety domain scores were significantly higher in children with dental caries (p<0.05). The adjusted Poisson regression model showed that household income, maternal education, mother's job status and breastfeeding time was significantly associated with ECOHIS scores. Regarding oral conditions, child caries experience was associated with worsening child and family quality of life (RR 2.21; 95% IC: 1.43-3.41). Conclusion: Our findings suggest that ECC, socioeconomic and maternal behaviors characteristics influence children's OHRQoL.